An efficient hydrogenation catalyst in sulfuric acid for the conversion of nitrobenzene to p-aminophenol: N-doped carbon with encapsulated molybdenum carbide. Issue 70 (10th August 2016) - Wang, Tao; Dong, Zhen; Cai, Weimeng; Wang, Yongzheng; Fu, Teng; Zhao, Bin; Peng, Luming; Ding, Weiping; Chen, Yi
Abstract : The transfer of catalytic function from molybdenum carbide to N-doped carbon for catalytic hydrogenation of nitrobenzene to p -aminophenol. Abstract : The transfer of catalytic function from molybdenum carbide to N-doped carbon has been tested by encapsulating molybdenum carbide with N-doped carbon using a one-pot preparation process. The outer layer of N-doped carbon, inert itself, exhibits high activity and excellent selectivity with molybdenum carbide as the catalyst for the hydrogenation of nitrobenzene to p -aminophenol in sulfuric acid.